Apoptosis and Molecular Targeting Therapy in Cancer. (12th June 2014) - Hassan, Mohamed; Watari, Hidemichi; AbuAlmaaty, Ali; Ohba, Yusuke; Sakuragi, Noriaki
Abstract : Apoptosis is the programmed cell death which maintains the healthy survival/death balance in metazoan cells. Defect in apoptosis can cause cancer or autoimmunity, while enhanced apoptosis may cause degenerative diseases. The apoptotic signals contribute into safeguarding the genomic integrity while defective apoptosis may promote carcinogenesis. The apoptotic signals are complicated and they are regulated at several levels. The signals of carcinogenesis modulate the central control points of the apoptotic pathways, including inhibitor of apoptosis (IAP) proteins and FLICE-inhibitory protein (c-FLIP). The tumor cells may use some of several molecular mechanisms to suppress apoptosis and acquire resistance to apoptotic agents, for example, by the expression of antiapoptotic proteins such as Bcl-2 or by the downregulation or mutation of proapoptotic proteins such as BAX. In this review, we provide the main regulatory molecules that govern the main basic mechanisms, extrinsic and intrinsic, of apoptosis in normal cells. We discuss how carcinogenesis could be developed via defective apoptotic pathways or their convergence. We listed some molecules which could be targeted to stimulate apoptosis in different cancers. Together, we briefly discuss the development of some promising cancer treatment strategies which target apoptotic inhibitors including Bcl-2 family proteins, IAPs, and c-FLIP for apoptosis induction.